Strategi Nafkah dan Relasi Sosial Rumahtangga Petani Tebu (Studi Kasus: Desa Jenar, Kecamatan Jenar, Sragen) - Budiyanti, Indah; Dharmawan, Arya Hadi (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2018)
ABSTRACT This research aims to analyze the livelihood strategies and social relation of sugarcane farmers household in Jenar Village, Subdistrict Jenar, Sragen Regency. This research will discuss about the capital living (natural capital, social capital, human capital, physical capital, and financial capital) on each farmer household and is used in building a strategy of living that will form the sustainable livelihood systems. In addition, this research discuss qualitatively about the social relation that are owned by a sugarcane farmers household to support the resilience of its economy. This research also discusses the influence of the livelihood capital towards the livelihood strategies of sugarcane farmers household. And then to look at how big the contribution livelihood source sugarcane farmers household income survival sugarcane farmers given that household sugarcane is a commodity that has the harvest for 1.5 years. This research use quantitative methods approach using survey instruments in the form of questionnaire, and qualitative research data by the method of depth interview.Key words: farmers household, livelihood assets, livelihood structure, social relation, strategies of living.————————–Â ABSTRAK Penelitian ini bertujuan untuk menganalisis Strategi dan Relasi Sosial Rumahtangga Petani Tebu di Desa Jenar, Kecamatan Jenar, Kabupaten Sragen. Penelitian ini akan membahas modal nafkah (modal alam, modal sosial, modal manusia, modal fisik, dan modal finansial) pada setiap rumahtangga petani dan digunakan dalam membangun strategi nafkah yang akan membentuk sistem penghidupan yang berkelanjutan. Selain itu, pada penelitian ini membahas secara kualitatif relasi sosial disetiap rumahtangga petani tebu untuk mendukung ketahanan ekonominya yang dilihat dari struktur nafkah. Penelitian ini juga membahas pengaruh modal nafkah terhadap strategi nafkah rumahtangga petani tebu. Serta melihat seberapa besar kontribusi sumber nafkah rumahtangga petani tebu dalam keberlangsungan hidup rumahtangga petani tebu mengingat bahwa tebu merupakan komoditi yang memiliki masa panen selama 1.5 tahun. Penelitian ini dilakukan menggunakan metode kuantitatif dengan pendekatan survey menggunakan instrumen berupa kuesioner, dan data penelitian kualitatif dengan metode wawancara mendalam.Kata Kunci : modal nafkah, Â rumahtangga petani , struktur nafkah, relasi sosial, strategi nafkah